GENETIC INSTABILITY IN NERVE SHEATH CELL TUMORS - Rainho, C. A.; Casartelli, C.; Barbierineto, J.; Rogatto, Silvia Regina [UNESP] (Soc Brasil Genetica, 1995)
After in vitro culture, we analyzed cytogenetically four acoustic nerve neurinomas, one intraspinal neurinoma and one neurofibroma obtained from unrelated patients. Monosomy of chromosomes 22 and 16 was an abnormality common to all cases, followed in frequency by loss of chromosomes 18 (three cases) and chromosomes 8, 17 and 19 (two cases). Trisomy of chromosome 20 was also detected in two cases. Structural rearrangements were detected at low frequencies, with del(10)(p12) being present in two cases. In addition, we observed cell subpopulations showing a certain degree of genetic instability, reflected by the presence of polyploid cells with inconsistent abnormalities, endoreduplications and telomeric associations resulting in dicentric chromosomes. It is probable that these cytogenetic abnormalities represent some kind of evolutionary advantage for the in vitro progression of nerve sheath tumors.